1999
DOI: 10.1021/jp9845930
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Sonolytic Degradation of Chlorinated Hydrocarbons:  Frequency Effects

Abstract: The kinetics of the sonolytic degradation of aqueous solutions of carbon tetrachloride and hexachloroethane (C2Cl6) were investigated at six different frequencies over the range from 20 to 1078 kHz. The rates of degradation of CCl4 and C2Cl6 were shown to increase with increasing frequency with optimal degradation rates at 500 kHz. At 205 kHz, the relative rates of sonolytic degradation of the three chlorinated methanes followed the order of CCl4 > CHCl3 > CH2Cl2. Hexachloroethane, which was formed as the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
156
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 34 publications
6
156
0
Order By: Relevance
“…The initial concentration was held constant in their experiments at 0.20 " 0.05 mM (~300 mg/L). Loss of CCl 4 due to volatilization was found to be less than 2% in separately run control experiments conducted in the absence of sonication [Hung and Hoffmann, 1999]. The pH after sonolytic degradation of CCl 4 were near 3.5; the principal products observed were OCl -, Cl -, C 2 Cl 4 , and C 2 Cl 6 [Hung and Hoffmann, 1999].…”
Section: Task 4 Conduct Continuous-flow Experiments For Degradation mentioning
confidence: 88%
See 4 more Smart Citations
“…The initial concentration was held constant in their experiments at 0.20 " 0.05 mM (~300 mg/L). Loss of CCl 4 due to volatilization was found to be less than 2% in separately run control experiments conducted in the absence of sonication [Hung and Hoffmann, 1999]. The pH after sonolytic degradation of CCl 4 were near 3.5; the principal products observed were OCl -, Cl -, C 2 Cl 4 , and C 2 Cl 6 [Hung and Hoffmann, 1999].…”
Section: Task 4 Conduct Continuous-flow Experiments For Degradation mentioning
confidence: 88%
“…Even with a small headspace in their reactor, loss of CCl 4 due to volatilization during sonolysis was negligible [Hua and Hoffmann, 1996a]. Loss of CCl 4 due to vapor stripping was found to be less than 2% in separate run control experiments conducted in the absence of ultrasonic irradiation [Hung and Hoffmann, 1999]. Performing control experiments conducted in the absence of ultrasonic irradiation, Suri et al [1999] observed negligible loss of TCE over a 25-minute period at 45 o C. Under ultrasonic irradiation, two experiments were conducted with 0-and 10-mL headspace, respectively; comparison of their results indicated that loss of TCE by volatilization was negligible (<2%) over a 20-minute period [Suri et al, 1999].…”
Section: Treatmentmentioning
confidence: 94%
See 3 more Smart Citations